Q22 Study of the suitability of a garden for use by clients with Huntington's disease, relatives and staff for therapy and leisure gardening. (29th August 2012) - Spring, J; Viera, M; Marsh, N; Bowen, C
Abstract : Background: Huntington's disease (HD) clients have gardened using an adapted gardening method in a garden with raised beds and containers for four years in London. Aims: Was the adapted garden a suitable and stimulating environment for leisure and therapy use, were activities appropriate to the residents' abilities, and what clinical problems or benefits were observed? Method: Views of clients (7), visitors (8) and staff (31) were captured with questionnaires (46) and interviews (5). A pictorial questionnaire accommodated clients' communication problems. Results: HD clients enjoyed growing flowers and vegetables. Labelling their plants with their name, being outside, in the sun and the quiet of the garden were important. They preferred red and pink flowers. Visitors used the garden for periods over an hour to meet with residents. Staff said gardening was a constructive, outdoor activity, promoted social interaction and clients achieved visible results. Half the staff said the activity was problem free and a third used the garden for therapy. Interviews with staff identified gardening as good physical work for HD clients and increased functional movement. The adapted method helps maintain residents skills, grading the task and using appropriate equipment. It posed cognitive challenges such as problem solving and sequencing. Conclusions: Gardening is a suitable activity for clients with Huntington's disease. Opportunities for therapy include motivation and a sensory rich garden environment, physical work, increased functional movement and cognitive challenges. Adapted gardening provides an enjoyable leisure activity that achieves visible results of flourishing plants in which clients take pride. Huntington's disease may affect colour vision with clients indicating a preference for the red end of the colour spectrum.